Dimer formation effect on the red-shift in fluorescent spectra of dye solutions - Saksit Sukprasong (2018)
© 2015 SPIE. The red-shift on fluorescent dyes spectra at high concentration was investigated by laser induce fluorescence technique. In this research, the fluorescent dyes (Rhodamine 6G, Rhodamine B, Fluorescein and Bromofluorescein) were used. The sample solutions were prepared with methanol solvent in the concentration range of 10 -5 to 10 -3 Molar and the temperature of sample solution was controlled at 25 °C by temperature control chamber. Then, the sample solution was illuminated by violet laser (405 nm) excitation source and the fluorescence spectra were recorded by CCD spectrometer. The result showed that the fluorescence spectra of all fluorescent dye solutions were dependent on concentration of fluorescent dyes. The position of fluorescence maximum intensity was shifted to a higher wavelength (red-shift) when the concentration increased because the dimer formation rate increases with increasing concentration, but the shifting of wavelength for each fluorescent dye solutions was different, which suggests the different rate of formation of dimer molecules in each fluorescent dye solutions.